Clinical investigation of former workers exposed to asbestos: the health surveillance experience of an Italian University Hospital - De Maria, Luigi; Pentimone, Floriana; Cavone, Domenica; Caputi, Antonio; Sponselli, Stefania; Fragassi, Francesco; Dicataldo, Francesco; Luisi, Vito; Delvecchio, Giuseppe; Giannelli, Gianmarco; Cafaro, Francesco; Sole, Stefano; et al. (Frontiers in Public Health, 2024)
Background: The need for health surveillance of formerly workers exposed to asbestos was provided by law in Italy after the ban on asbestos in 1992. Objectives: We describe the results of the health surveillance of exposed former workers conducted for 27 years, from 1994 to 2020, at the Operative Unit of Occupational Medicine of the University Hospital of Bari. Materials and Methods: We adopted the health surveillance protocol lately validated at national level in 2018. Results: A total of 1405 formerly exposed workers were examined. It was possible to proceed with the diagnosis of pathologies in 339 cases (24% of the cohort subjected to surveillance); for some of them, a diagnosis of multiple pathologies was made. Specifically, pleural plaques were diagnosed in 49.2% of 339 cases, asbestosis in 35.9% of cases, malignant pleural mesothelioma (MPM) in 20.3% of cases, mes-othelioma of the vaginal tunic of the testis in 9.1% of cases, lung cancer in 5.8% of cases, and laryngeal cancer in 0.8%. Conclu-sions: Despite the 1992 asbestos ban, asbestos-related diseases are still a serious public health problem. It is important to es-tablish criteria for which the health surveillance of formerly exposed workers allows the minimization of costs, reduction of the amount of invasive examinations and optimization of possible achievable results.